Jesse Stone : Death in Paradise - Harmon, Robert, director; Selleck, Tom, 1945-; Brady, Orla, 1961-; McHattie, Stephen; Parker, Robert B 1932- (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
A hard-edged former Los Angeles cop becomes police chief in a small New England town and goes up against the mob as he investigates the murder of a teenage girl.
Based on the novel by Robert B. Parker.
Tom Selleck, Orla Brady, Stephen McHattie, Viola Davis.
MPAA rating: Not rated.
DVD, Dolby digital 5.1 surround.
In English, French, Portuguese, or Thai with optional Chinese, English, French, Portuguese, Spanish, or Thai subtitles.
Closed-captioned.
Keywords: Parker, Robert B -- 1932- -- Film and video adaptations; Stone, Jesse (Fictitious character) -- Drama; Murder -- Investigation -- Drama; Police chiefs -- Drama; Detective and mystery films; Made-for-TV movies; Video recordings for the hearing impaired; Based on the book; Feature films; Detective films; Mystery films